The Effect of Foreign Exchange Transaction on the Performance of Nigerian Banks - Manyo, Takon Samuel; Sabina, Nsofor Ebele; Ugochukwu, Ugwuegbe Sebastine (IJRDO - Journal of Business Management, 2016)
This study investigated the effect of foreign exchange transaction on the profitability of Nigerianbanks for the period of 2010 to 2014. The study employed annual data generated from theannual report of ten (10) publicly quoted banks in Nigeria. To test for the properties of paneldata, Levin, Lin and Chu (2002), Breitung (2000), Im, Pesaran and Shin (2003), Hadri (2000)and Maddala and Wu (1999) test of panel unit root were deployed. Based on the popularity ofthe result we concluded that the variables are integrated of order one I(1). The result of Kaopanel co-integration test indicates that there exists a long run relationship between the variablesunder study. The result of the DOLS revealed that foreign exchange income has a negative andinsignificant effect on the profitability of Nigerian banks for the period. Total asset which wasused as a control variable was shown to exert positive impact on the profitability of Nigerianbanks, while total equity has a negative effect on profitability of banks in Nigeria for the sameperiod under study. The studies recommend that CBN and other monetary authorities shouldmonitor the activities of the banks to ensure that they don’t charge high premium for selling orbuying foreign exchange to their customers. Banks should enhance their assets base so as toincrease profitability.